Recent advancements in skin cancer treatment: a critical review - Rajat Goyal; Shaheen Husain; Kashish Wilson; Hitesh Chopra; Rakesh Pahwa; Mathumalar Loganathan; Rohit Sharma (Open Exploration Publishing Inc., 2023)
The prevalence of skin cancer has increased hastily in the recent decade for both kinds of melanoma and non-melanoma skin cancer. Skin cancers mostly encompass keratinocyte cancers: cutaneous squamous cell carcinoma, basal cell carcinoma, and melanoma. This review discusses the recent advancements in the treatment of skin cancer. In addition to chemotherapy, immunotherapy, targeted therapy, and photodynamic therapy (PDT), there are several other therapies for skin cancer. Additionally, PDT use in combination with chemotherapy, radiation, immunotherapy, and surgery is being actively investigated. This review will specifically address the pathophysiology of skin cancer, diagnostic approaches, and current therapies used in the topical treatment of skin cancers and introduce emerging treatment using nanotechnology that may be beneficial for these indications.